Markers of Non-alcoholic Fatty Liver Disease Among Metabolically Healthy and Unhealthy Obese Individuals - Şencay Yıldız Şahin; Saliha Yusufoğlu; Sevim Özdemir; Mehmet Koçak; Hayriye Esra Ataoğlu (Boğaziçi Tıp Dergisi, 2023)
INTRODUCTION: Obesity, which is defined as excessive and abnormal accumulation of adipose tissue, can lead to various systemic diseases beyond the deterioration of the quality of life of individuals. In this study, we aimed to compare the biochemical parameters, the presence of hepatosteatosis, non-invasive liver fibrous scores (NAFLD), and common carotid artery (CCA) media thickness in metabolically healthy obese (MHO) and metabolically unhealthy obese (MUHO). METHODS: Charts of patients who were admitted to the internal medicine outpatient clinic between June 2018 and June 2019 were retrospectively evaluated. Patients with body mass index ≥30 kg/m2 were evaluated for inclusion in the study. Participants were divided into two groups as MHO and MUHO, according to the Third National Health and Nutrition Examination Survey III criteria. The presence of liver fibrosis was calculated using NAFLD fibrosis score (NFS) and Fib-4 score. Patients categorized as MHO and MUHO were compared according to demographic characteristics, biochemical parameters, and radiological findings. RESULTS: Totally, 123 obese patients were enrolled into the study, and 95 patients were classified as MUHO. CCA was measured as 0.6 mm in MHO and 0.7 mm in MHUO, and the difference was statically significant in favor of MHO (p<0.001). Homeostatic model assessment of insulin resistance (HOMA-IR), insulin level, and triglyceride/glucose index (TyG) index were significantly higher in MUHO. The difference of Fib-4 indexes in MHO and MUHO was not statistically significant (p=0.100). However, NFS was significantly better in MHO (p<0.001). DISCUSSION AND CONCLUSION: The present study showed that almost four out of five obese patients were classified as MUHO. In addition, levels of glutamyl transferase, HOMA-IR, insulin, and TyG index were significantly higher in MUHO in comparison with MHO. Moreover, MUHO cases had significantly higher CCA media thickness levels, liver size, and worse NFS.